The following questions are practice problems associated with the
lecture material on the subject of Boolean Algebra. These problems
have appeared on past exams in this course; variation of them will be found
on your first exam.
(Go back to homepage.)

Which of the following relationships represents the dual of the
Boolean property x + x' = 1? (Note: * = AND, + = OR)
 x'* x = 1
 x * x'= 1
 x + x'= 0
 x * x'= 0
 x'* x = 0

An equivalent representation for the Boolean expression
A' + 1 is
 A
 A'
 1
 0

Simplification of the Boolean expression
(A+B+C)(D+E)' + (A+B+C)(D+E) yields which of the following results?
 A + B + C
 D + E
 A'B'C'
 D'E'
 None of the above

Given the function F(A,B,X,Y) = AB + X'Y, the most simplified
Boolean representation for F' is
 (AB)' + (X'Y)
 A'*B' + XY'
 (A'+ B')(X + Y')
 (AB + X'*Y)'
 (AB)'(X'*Y)'

An equivalent representation for the Boolean expression
A + A' is
 1
 0
 A
 A'
 A'*A

Simplification of the Boolean expression
AB + ABC + ABCD + ABCDE + ABCDEF yields which of the following results?
 ABCDEF
 AB
 AB + CD + EF
 A + B + C + D + E + F
 A + B(C+D(E+F))

Given the function F(X,Y,Z) = XZ + Z(X'+ XY), the equivalent, most
simplified Boolean representation for F is
 Z + YZ
 Z + XYZ
 XZ
 X + YZ
 none of the above

Given that F = A'B'+ C'+ D'+ E', which of the following represent
the correct expression for F'?
 F'= A+B+C+D+E
 F'= ABCDE
 F'= AB+CDE
 F'= AB+C'+D'+E'
 F'= (A+B)CDE

Simplification of the Boolean expression (A+B+C) + (A+B+C)'(D+E)
yields which of the following results?
 A + B + C
 D + E
 A'*B'*C'
 D'E'
 A+B+C+D+E

Which of the following relationships represents the dual of the
Boolean property x + x'y = x + y Choose the best answer.
 x'(x + y') = x'*y'
 x(x'y) = xy
 x*x' + y = xy
 x'(xy') = x'*y'
 x(x' + y) = xy

Simplification of the Boolean expression
(A + B)'*(C + D + E)' + (A + B)' yields which of the following results?
 A + B
 A'B'
 C + D + E
 C'D'E'
 A'B'C'D'E'

Given that F = (A + B'+ C)(D + E), which of the following
represents the only correct expression for F'?
 F' = A'BC'+ D'+ E'
 F' = AB'C + DE
 F' = (A'+ B + C')(D'+ E')
 F' = A'BC' + D'E'
 F' = (A + B'+ C)(D'+ E')

Simplification of the Boolean expression AB + A(BC)' yields which
of following results?
 A
 BC
 B
 AB
 (BC)'

Simplifing (AB)' + A'B to most basic form yields which of the
following expressions?
 A'
 B'
 A+B
 B
 (AB)'
